Perbandingan Media Pembelajaran Flashcard dengan Gambar Berseri dalam Keterampilan Menulis Karangan Bahasa Jerman Mahasiswa Program Studi Pendidikan Bahasa Jerman FBS UNM - Ambo Dalle; Muhammad Anwar; Wahyu Kurniati Asri (Seminar Nasional LP2M UNM, 2019)
Abstract. This research aims to describe the comparison of Flashcard learning media and serial pictures in writing skills in German students. This research was designed in the form of experimental research. The subjects of this study were 56 students consisting of 28 students of class A as experimental class 1 with the application of Flashcard media and 28 students of class B as experimental class 2 with the application of media of serial pictures. Data collection was carried out through a German writing skills test. The results obtained in the two experimental groups showed that the average learning outcomes of German writing skills after being given a Flashcard treatment was 66.64 and the radiant images were 61.5. Data were then analyzed using t-test analysis and showed that 2,107> tt 2,005 at the significant level of 0.05. The results showed that Flashcard learning media and serial pictures influence the German writing skills. Although the achievement of the learning outcomes of students' experimental group 1 (class A) learning skills taught using Flashcard learning media is superior to the experimental group 2 (class B) that is taught using serial learning media. However, the use of both media is equally effective and has increased student learning outcomes after its application in learning Keywords: Learning Media, Flashcard, Series Picture, German language, Writing